Black Campaign Social Media sebagai Komunikasi Aktor Politik dalam Pemilihan Umum di Indonesia - Inke Nur Dewanti (JURNAL LENSA MUTIARA KOMUNIKASI, 2022)
This research is intended to show how black campaigns are a communication medium for political actors in the general elections that took place in Indonesia, especially 2019. One of the black campaigns that was born was with the emergence of “cebong” and “kampret” who provoked social media. In addition, the media that contribute to the spread of the black campaign are not far from Facebook, Twitter, Instagram, to chat media such as WhatsApp. The method used in this research is a literature study. Later there are several ways that can be done to avoid black campaigns by taking repressive and preventive actions using law enforcement. In the discussion of this journal, it was found that media literacy is one of the supporting tools to help educate the public in political life. Media literacy can also be campaigned from an early age for the people to avoid hoaxes and disinformation that are increasingly rampant and increase political participation.